Predicting violence in newly admitted inmates: a lens model analysis of staff decision making - Cooper, Robert P. (Criminal justice and behavior, 1990)
Ten experienced psychologists and 11 case managers within the Federal Bureau of Prisons employed 17 demographic and biographical variables as cues to forecast violence during the first 6 months of incarceration of 33 male inmates at a medium-security federal correctional institution. Low levels of reliability were found among individual judges' forecasts, but high agreement was found for their composite judgments. These professionals' forecasts of inmates' violence showed low accuracy. Lens model analyses suggested that although forecasts and actual violence were both linearly predictable from the independent variables, low accuracy may have resulted because professionals failed to weight these factors optimally. Further analyses suggested that inmates showing violence at follow-up were younger, were more likely to come from nonurban areas, and had a history of more prior arrests and convictions than did inmates who did not show violence in prison. Implications for improving accuracy at predicting short-term violence are discussed